Lee Harker's Character Development in “Longlegs” Movie - Kusuma, Pradipta Hadi; Aulia, Rania Farah; Faisal, Faisal (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2025)
This article examines Lee Harker's character growth in movie "Longlegs", concentrating on her emotional journey and the significance of family ties. The study looks at how Harker's tragic history and psychic talents influence her identity as an FBI agent, drawing on Hurlock's theory on emotional determinants. The movie is divided into three sections, each of which shows a different aspect of Harker's personality as she faces Longlegs, the serial murderer. The results demonstrate how Harker's journey exemplifies more general concepts of morality, autonomy, and the effects of hereditary trauma. The emotional burden of her family history affects her decision-making and interpersonal interactions while she conducts her inquiry, highlighting the significance of emotional intelligence in overcoming hardship. Ultimately, this approach emphasizes how important story is as a tool for examining nuanced human experiences in both literature and film. The article's focus on Harker's character arc illustrates the importance of storytelling in forming social ideals and interpersonal relationships while also enhancing our knowledge of how tales reflect and impact views of trauma and personal progress.